Brain activation during the observation of real soccer game situations predicts creative goal scoring. Issue 7 (24th March 2021) - Rominger, Christian; Koschutnig, Karl; Memmert, Daniel; Papousek, Ilona; Perchtold-Stefan, Corinna M; Benedek, Mathias; Schwerdtfeger, Andreas R; Fink, Andreas
Abstract: Creativity is an important source of success in soccer players. In order to be effective in soccer, unpredictable, sudden and at the same time creative (i.e. unique, original and effective) ideas are required in situations with high time pressure. Accordingly, creative task performance in soccer should be primarily driven by rapid and automatic cognitive processes. This study investigated if functional patterns of brain activation during the observation/encoding of real soccer game situations can predict creative soccer task performance. A machine learning approach (multivariate pattern recognition) was applied in a sample of 35 experienced male soccer players. The results revealed that brain activation during the observation of the soccer scenes significantly predicted creative soccer task performance, while brain activation during the subsequent ideation/elaboration period did not. The identified brain network included areas such as the angular gyrus, the supramarginal gyrus, the occipital cortex, parts of the cerebellum and (left) supplementary motor areas, which are important for semantic information processing, memory retrieval, integration of sensory information and motor control. This finding suggests that early and presumably automatized neurocognitive processes, such as (implicit) knowledge about motor movements, and the rapid integration of information from different sources are important for creative task performance in soccer.